Actividad antimicrobiana In Vitro del oleato de Allium sativum (ajo) frente a cepas de Staphylococcus aureus y Candida albicans - Novoa Melchor, Milagros Vanessa; Zapata Guerra, Ittalo Alonso (PE, 2026)
El objetivo de la investigación fue determinar la actividad antimicrobiana in vitro del oleato de Allium sativum (ajo) frente a cepas de Staphylococcus aureus y Candida albicans. El estudio fue de tipo experimental, con enfoque cuantitativo, diseño transversal y prospectivo. La muestra estuvo conformada por 40 placas Petri distribuidas en grupos experimentales y controles, utilizando cepas de Staphylococcus aureus ATCC 25923 y Candida albicans ATCC 10231. Los resultados mostraron que el oleato de ajo al 50 % presentó mayor actividad antimicrobiana, con halos de inhibición promedio de 16.38 mm frente a Staphylococcus aureus y 18.11 mm frente a Candida albicans, mientras que la concentración al 100 % evidenció menor actividad. Se encontraron diferencias estadísticamente significativas entre los tratamientos (p < 0.05). Se concluye que el oleato de Allium sativum posee actividad antimicrobiana in vitro, siendo más eficaz a una concentración del 50 %, por lo que constituye una potencial alternativa terapéutica complementaria frente a infecciones bacterianas y fúngicas.

The objective of this research was to determine the in vitro antimicrobial activity of Allium sativum (garlic) oleate against Staphylococcus aureus and Candida albicans strains. The study was experimental, with a quantitative approach, and a cross-sectional, prospective design. The sample consisted of 40 Petri dishes distributed into experimental and control groups, using Staphylococcus aureus ATCC 25923 and Candida albicans ATCC 10231 strains. The results showed that the 50% garlic oleate concentration exhibited the greatest antimicrobial activity, with average inhibition zones of 16.38 mm against Staphylococcus aureus and 18.11 mm against Candida albicans, while the 100% concentration showed lower activity. Statistically significant differences were found between treatments (p < 0.05). It is concluded that Allium sativum oleate has antimicrobial activity in vitro, being most effective at a concentration of 50%, thus constituting a potential complementary therapeutic alternative against bacterial and fungal infections.
In vitro antimicrobial activity of Allium sativum (garlic) oleate against Staphylococcus aureus and Candida albicans strains
Keywords: Allium sativum; Staphylococcus aureus; Candida albicans; http://purl.org/pe-repo/ocde/ford#3.01.05